(untitled) (Al-Academy, 2025)
Islamic-style design is characterized by an emphasis on simplicity, fine details, curved lines, harmonious geometric shapes, warm colors, and distinctive Islamic patterns. The Islamic style is also characterized by attention to complex decorative details that contain symbols and various geometric shapes, and Arabic calligraphy is used in writing and design. The Islamic style of design and decoration is applied in the design of mosques, palaces, hotels, resorts, interiors and exteriors, and forms an important part of the cultural and artistic heritage of Muslims. The research aims to: 1- Shedding light on the precious artistic value of the elements of the Holy Mosque in Mecca and the extent of the possibility of using them in designs within the Arab councils of the residence 2- Using computer programs to create designs inspired by the artistic elements of the Holy Mosque of Mecca to beautify the living rooms. 3- Making innovative designs for some residence halls in order to convey the aesthetic idea of the artistic units of the Holy Mosque of Mecca. As for the importance of the research: 1- Identify the aesthetic values of the artistic units in the Grand Mosque of Mecca 2- Taking advantage of the aesthetic values of some artistic units in the Holy Mosque of Mecca for the innovative design of some rooms of the residence. Results: 1- Achieving a new vision of the decorative elements of the Holy Mosque of Mecca, interior design 2- This design departs from the traditional Islamic style to benefit and does not have any of the artistic elements of the Holy Mosque in Mecca. As for the recommendations: 1- The researcher recommends the importance of focusing on the interior design of Islamic-style housing based on the ancient Islamic legacies of the Holy Mosque of Mecca. 2- How to conduct an analytical study to identify the precise technical elements and foundations of the Holy Mosque in Mecca, as well as the Holy Mosque in Medina, since the Prophet’s mission until today